2013
DOI: 10.1016/j.chemphys.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of hydrocarbonaceous overlayers important in metal-catalysed selective hydrogenation reactions

Abstract: Abstract.The hydrogenation of alkynes to alkenes over supported metal catalysts is an important industrial process and it has been shown that hydrocarbonaceous overlayers are important in controlling selectivity profiles of metal-catalysed hydrogenation reactions. As a model system we have selected propyne hydrogenation over a commercial Pd(5%)/Al 2 O 3 catalyst. Inelastic neutron scattering studies show that the C-H stretching mode ranges from 2850-3063 cm -1 , indicating the mostly aliphatic nature of the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Dry reforming of two differently treated Ni/Al 2 O 3 catalysts showedm ostly aliphatic carbon on one sample, whereas the other sample presented mostly aromatic carbon.Q uantification of hydrogen in the hydrocarbonaceous overlayers of Ni/Al 2 O 3 catalysts showedC /H ratios ranging from 160:1 to 11 690:1;t hus highlighting the good hydrogen cycling capabilitieso ft he catalysts, butp oor (and differ-ent) carbon cycling capabilities. [44][45][46] In af ollow-up study within the same group, [49] INS was used to characterize a Pd(5 %)/Al 2 O 3 catalyst after propyne hydrogenation. Contrary to what the authors found on the Ni/Al 2 O 3 catalysts after dry reforming of methane, the C/H ratio was much smaller (1:1.8) and typical of aliphatic species.…”
Section: Hydrogenous Speciesr Elevant For Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Dry reforming of two differently treated Ni/Al 2 O 3 catalysts showedm ostly aliphatic carbon on one sample, whereas the other sample presented mostly aromatic carbon.Q uantification of hydrogen in the hydrocarbonaceous overlayers of Ni/Al 2 O 3 catalysts showedC /H ratios ranging from 160:1 to 11 690:1;t hus highlighting the good hydrogen cycling capabilitieso ft he catalysts, butp oor (and differ-ent) carbon cycling capabilities. [44][45][46] In af ollow-up study within the same group, [49] INS was used to characterize a Pd(5 %)/Al 2 O 3 catalyst after propyne hydrogenation. Contrary to what the authors found on the Ni/Al 2 O 3 catalysts after dry reforming of methane, the C/H ratio was much smaller (1:1.8) and typical of aliphatic species.…”
Section: Hydrogenous Speciesr Elevant For Catalysismentioning
confidence: 99%
“…Reprintedw ith permission from ref. [49].Copyright2 013 Elsevier. ChemSusChem 2019, 12,93-103 www.chemsuschem.org and the intensities of those corresponding to vinylidene species increased.…”
Section: Hydrogenous Speciesr Elevant For Catalysismentioning
confidence: 99%
“…However, the spectrum of the reacted sample exhibited a poor signal:noise ratio, indicating a low degree of hydrogen retention by the catalyst. A previous use of INS by Warringham and co-workers to examine the hydrogenation of propyne over alumina-supported Pd catalysts showed how the enhanced sensitivity of the MER-LIN spectrometer could be used to acquire the vibrational spectra of minority species, albeit at reduced resolution compared to that attainable with the MAPS spectrometer [30]. Consequently, in an attempt to obtain superior spectra, both the dried and reacted samples were also run on the MERLIN spectrometer using the low resolution S chopper package operating at incident energies of 4840 (frequency = 600 Hz) and 2016 cm -1 (frequency = 400 Hz) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Further, inelastic neutron scattering (INS) measurements on various Pd supported catalysts has shown the presence of a beta hydride phase to have a noticeable effect on nitrobenzene hydrogenation activity [24]. Recently, INS has also detected the presence of a β-PdH phase during conditions that support selective propyne hydrogenation over a supported Pd catalyst [25].…”
Section: Introductionmentioning
confidence: 99%